How immigrant optimism shapes educational transitions over the educational life course–Empirical evidence from Germany - Busse, Robin; Scharenberg, Katja (Frontiers in Education, 2022)
Compared to natives, young adults with an immigrant background are more likely to choose academic education over vocational education and training (VET). Our study investigates ethnic choice effects at different stages of the educational system. Based on longitudinal data from the German National Educational Panel Study (NEPS), we found that immigrant youths – when controlling for achievement and social background – were more likely to attend academic tracks in Grade 9, have higher participation rates in academic tracks at the upper-secondary level, are less likely to choose VET after lower-secondary education as well as after upper-secondary education, and switch more often to higher education after achieving an upper-secondary degree. Mediation analyses confirmed that these effects were largely shaped by differences in educational and occupational aspirations. Our study provides detailed insights into the transition pathways at different educational stages and the relevant mechanisms driving migration-specific choice effects. As ethnic choice effects are empirically well documented in international research, our investigation may contribute to a deeper understanding of educational inequalities in other European countries.